Brief Report: Reconstruction of Joint Hyaline Cartilage by Autologous Progenitor Cells Derived from Ear Elastic Cartilage. (19th February 2014) - Mizuno, Mitsuru; Kobayashi, Shinji; Takebe, Takanori; Kan, Hiroomi; Yabuki, Yuichiro; Matsuzaki, Takahisa; Yoshikawa, Hiroshi Y.; Nakabayashi, Seiichiro; Ik, Lee Jeong; Maegawa, Jiro; Taniguchi, Hideki
Abstract: In healthy joints, hyaline cartilage covering the joint surfaces of bones provides cushioning due to its unique mechanical properties. However, because of its limited regenerative capacity, age- and sports-related injuries to this tissue may lead to degenerative arthropathies, prompting researchers to investigate a variety of cell sources. We recently succeeded in isolating human cartilage progenitor cells from ear elastic cartilage. Human cartilage progenitor cells have high chondrogenic and proliferative potential to form elastic cartilage with long-term tissue maintenance. However, it is unknown whether ear-derived cartilage progenitor cells can be used to reconstruct hyaline cartilage, which has different mechanical and histological properties from elastic cartilage. In our efforts to develop foundational technologies for joint hyaline cartilage repair and reconstruction, we conducted this study to obtain an answer to this question. We created an experimental canine model of knee joint cartilage damage, transplanted ear-derived autologous cartilage progenitor cells. The reconstructed cartilage was rich in proteoglycans and showed unique histological characteristics similar to joint hyaline cartilage. In addition, mechanical properties of the reconstructed tissues were higher than those of ear cartilage and equal to those of joint hyaline cartilage. This study suggested that joint hyaline cartilage was reconstructed from ear-derived cartilage progenitor cells. It also demonstrated that ear-derived cartilage progenitor cells, which can be harvested by a minimally invasive method, would be useful for reconstructing joint hyaline cartilage in patients with degenerative arthropathies. Stem Cells   2014;32:816–821